Dakwah’s Communication Strategies in the Digital Age: the Influence of Alaydrus’s Platform of Instagram - Faishol, Muhammad; Zuhro, Fathimatuz (Jurnal Kajian Manajemen Dakwah, 2024)
Divinity faces great challenges because of the diverse challenges and the intensity of changing times that each time raise new questions and studies, and given the diversity of human needs and interests that now tend to be more critical. One of the da’i who has been praising using the existing technology is Ustadzah Halimah Alaydrus on his Instagram account. In his account he not only video, but also answers to the problems experienced by his followers so not rarely they interact by leaving a comment on the comment column. The purpose of this research is to learn about the strategy of Ustadzah Halimah Alaydrus and its influence on his Instagram account. This research uses a qualitative approach to understand the strategy in depth. The result of this research is to know the performance and also the influence of Ustadzah Halimah Alaydrus.